Trophic sources and linkages to support mesozooplankton community in the Kuroshio of the East China Sea. (30th July 2020) - Karu, Fukutaro; Kobari, Toru; Honma, Taiga; Kanayama, Takeru; Suzuki, Koji; Yoshie, Naoki; Kume, Gen
Abstract: Many migratory fishes reproduce and recruit around the Kuroshio, and their survival of early life stages is supported by mesozooplankton. Mesozooplankton standing stocks and productivity equivalent to those on the continental shelf have been found in the Kuroshio; however, there is limited information on trophic sources and linkages to support the mesozooplankton community. Here, we evaluate mesozooplankton feeding on protists and their trophodynamics importance by removal bottle experiments in the Kuroshio of the East China (ECS‐Kuroshio). Pico‐ and nano‐autotrophs dominated chlorophyll a concentrations throughout the study sites across the continental shelf, within the Kuroshio path and in adjacent waters. Calanoid and poecilostomatoid copepods comprised more than 85% of mesozooplankton biomass. Significant mesozooplankton ingestion rates were found for nano‐autotrophs based on size‐fractionated chlorophyll; for haptophytes, chrysophytes, chlorophytes, and diatoms from pigment‐based phytoplankton analysis; and for naked ciliates in the microzooplankton. Based on the estimates of individual carbon budgets, nano‐autotrophs and naked ciliates ingested by mesozooplankton composed 39% of their food requirements, suggesting other available prey like nano‐heterotrophs. These results imply that mesozooplankton ingestion in the ECS‐Kuroshio has great impacts on protozoan and phytoplankton communities and their major trophic pathways are from nano‐sized auto‐ and heterotrophs and ciliates to copepods.